Customer loyalty to Islamic banks: Evidence from Indonesia - Bayu Arie Fianto; Christopher Gan; Tika Widiastuti; Raditya Sukmana (Cogent Business & Management, 2020)
This study identifies determinants of customer loyalty to Islamic banking in Indonesia using a structural equation model (SEM) and confirmatory factor analysis (CFA). Data of 362 respondents from two cities of East Java Indonesia have been used to determine the factors of customer loyalty of state-owned and private Islamic bank. The findings suggest that the customers have different perceptions about state-owned and private Islamic banks; with customer engagement is the strongest influence on customer loyalty in state-owned and customer satisfaction is the strongest influence in private Islamic banks.